1999
DOI: 10.1103/physrevlett.82.1281
|View full text |Cite
|
Sign up to set email alerts
|

ESR Study of the Opening and Closing of the Field-Induced Gap inNH4CuCl3

Abstract: ESR measurements in the double-chain compound NH 4 CuCl 3 , which has magnetization plateaus at one-quarter and three-quarters of the saturation magnetization, have been performed in magnetic fields up to 30 T in the frequency range ϳ95 762 GHz. It is found that the frequency versus field diagrams for H k a and H k b coincide when normalized by the g factors. In each plateau region, a pair of excitations expressed as v g͑H 2 H lc ͒ and v g͑H hc 2 H͒ are observed, where H lc and H hc are the lower and higher ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
5
26
0
Order By: Relevance
“…39,40) Recently, Ohta and his coworkers 41) have investigated the pressure dependence of the gap in KCuCl 3 up to 3.2 kbar by means of high-field and high-frequency ESR. Their result is in accordance with our result, as shown in Fig.…”
Section: 24)mentioning
confidence: 99%
“…39,40) Recently, Ohta and his coworkers 41) have investigated the pressure dependence of the gap in KCuCl 3 up to 3.2 kbar by means of high-field and high-frequency ESR. Their result is in accordance with our result, as shown in Fig.…”
Section: 24)mentioning
confidence: 99%
“…3), detected by ESR measurements. 3 In the 1/4-plateau region, a ω 1 -mode increases linearly with the field, while the ω 2 -mode decreases and goes soft at H c2 . In this field region, each A dimer is fully polarized by the field, and is in the lowest lying triplet | ↑↑ , while the configuration of B dimer is dominated by the singlet component.…”
mentioning
confidence: 99%
“…2 For NH 4 CuCl 3 , Kurniawan et al performed ESR experiments which revealed that NH 4 CuCl 3 has a finite excitation gap in the plateau regions. 3 By studying specific heat, they found AF order already at zero field and suggested a phase diagram in finite fields containing three magnetically ordered phases. 4 The origin of magnetization plateaus has attracted much interest recently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Matsumoto [21] theoretically suggested that there are three distinct magnetic dimer sublattices with different exchange interactions in NH 4 CuCl 3 , in contrast to the isostructural KCuCl 3 and TlCuCl 3 , and reproduced well the magnetization plateaus and field dependence of the magnetic resonance frequencies observed in ESR measurements [22,23] by his model. Successive structural phase transitions which may indicate the creation of such distinct magnetic dimers have been observed at low temperatures by means of various kind of experiments [24,25,26,27,28] while the isostructural KCuCl 3 and TlCuCl 3 undergo no structural phase transitions at low temperature.…”
mentioning
confidence: 54%